2016
DOI: 10.1515/bhk-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a nine-day alpine ski training programme on the postural stability of people with different levels of skills

Abstract: SummaryStudy aim: In alpine skiing, balance is one of the key elements that determine the effectiveness of the ride. Because of ski boots, the foot and ankle joint complex is excluded from the process of maintaining the stability of the body. The aim of the study was to determine to what extent a few days of skiing activities and the level of technical skills affect the skiers' level of postural stability. Material and methods:The study involved 10 beginner (20.7 ± 1.1 years, 76.4 ± 8.7 kg, 184.4 ± 6.1 cm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…A recent review and meta-analysis highlights the specificity of balance training (Kümmel et al, 2016). From this perspective, the adaptations in postural control obtained through alpine skiing may be expected to be situation specific, for example, specific to wearing a ski boot (Noé et al, 2009; Bottoni et al, 2014; Staniszewski et al, 2016). Improvements in postural stability may also relate less to laboratory tests for static or dynamic stability (Cigrovski et al, 2017, Panjan et al, 2016), but may have a stronger effect on postural control during sliding or slipping.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review and meta-analysis highlights the specificity of balance training (Kümmel et al, 2016). From this perspective, the adaptations in postural control obtained through alpine skiing may be expected to be situation specific, for example, specific to wearing a ski boot (Noé et al, 2009; Bottoni et al, 2014; Staniszewski et al, 2016). Improvements in postural stability may also relate less to laboratory tests for static or dynamic stability (Cigrovski et al, 2017, Panjan et al, 2016), but may have a stronger effect on postural control during sliding or slipping.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the participant's gender or prior skiing experience, "substantial improvements in balance performance of physically active young people after seven days of supervised alpine skiing with experts" (Wojtyczek et al, 2014, p. 38). Among skiers, Staniszewski et al (2016) found that, while there was no significant difference in balance parameters between beginner and expert skiers, beginner skiers showed "significantly more differences and changes in the parameters of the stability of the body" when comparing measures between balance wearing ski boots and while barefoot (p. 30). Specifically, beginner skiers demonstrated improved balance in ski boots and worsened balance while barefoot after the program.…”
Section: Balance and Motor Skillsmentioning
confidence: 96%
“…Both studies of skiing participants were interested in differences in balance before and after participating in a ski program. The studies examined whether a multi-day program would affect general balance performance (Wojtyczek et al, 2014) or postural stability (Staniszewski et al, 2016). Amongst snowboarders, one study examined the change in static and dynamic body stability of beginner and advanced participants after engaging in a nine-day snowboard instruction program (Staniszewski et al, 2017).…”
Section: Balance and Motor Skillsmentioning
confidence: 99%
“…The article points out that the difference between skiing balance and daily activity balance which is in skiing balance, athletes should adjust the height of the centre of gravity according to different techniques to complete the action, especially with the advancement of ski techniques such as carving, skiers need a strong core force to control the roll edge change and front and back balance, and accurately cut the skis to achieve the best sports performance 18 . Through Staniszewski’s 7 research also can be determined that good balance ability has a positive impact on skiing, regardless of skiers’ technical level 7 . At present, there are few literatures about balance research in skiing, and the test methods for evaluating balance do not all have enough differentiation ability.…”
Section: Background and Summarymentioning
confidence: 99%